1994
DOI: 10.1073/pnas.91.11.4965
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor variable region gene usage by CD4+ and CD8+ T cells in bronchoalveolar lavage fluid and peripheral blood of sarcoidosis patients.

Abstract: Sarcoldosis is a chroniconaing graulomatous disease of unknown etiology. An accumulation of CD4+ T cells in the alveolar space ofthe lungs is a characteristic feature of the disease. We have in this study analyzed T-cell receptor (TCR) variable region (V) (6)(7)(8)(9)(10)(11)(12). Also, in the recognition of so-called superantigens, T lymphocytes bearing particular TCR Vp gene segment products are of critical importance (reviewed in ref. 13).We have previously described a preliminary correlation between a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
2

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 21 publications
5
100
2
Order By: Relevance
“…In our evaluation of 8 sarcoidosis patients, 4 of whom were positive for DRB1*03, we did not detect any CD4ϩ BV3ϩ expansion (31). We also did not find expansions of CD4ϩ BV3ϩ cells in BAL fluid samples from patients with allergic asthma either before or after allergen challenge (3 of 8 patients studied were DRB1*03 positive) (21).…”
Section: Discussionmentioning
confidence: 46%
“…In our evaluation of 8 sarcoidosis patients, 4 of whom were positive for DRB1*03, we did not detect any CD4ϩ BV3ϩ expansion (31). We also did not find expansions of CD4ϩ BV3ϩ cells in BAL fluid samples from patients with allergic asthma either before or after allergen challenge (3 of 8 patients studied were DRB1*03 positive) (21).…”
Section: Discussionmentioning
confidence: 46%
“…Together with HLA and T-cell receptor (TCR) genes, Gm and km allotypes account for the most informative triad of genes involved in immune-related diseases, but so far have not been extensively studied in sarcoidosis. GRUNEWALD et al [12] reported a positive association between the TCR variable region a2.3+, in CD4+ lung T-cells and the HLA-DR3(17),DQ2 haplotype in sarcoidosis.…”
mentioning
confidence: 99%
“…AV2S3z CD4z T-cells accumulating in the lungs, was previously identified only in HLA-DR17 positive Scandinavian Caucasian sarcoidosis patients [20,22]. In fact, the association between lung accumulated CD4z AV2S3z T-lymphocytes and HLA-DR17 in Scandinavian patients with pulmonary sarcoidosis is extremely strict, provided there is an active disease [20,22].…”
Section: Discussionmentioning
confidence: 95%
“…AV2S3z CD4z T-cells accumulating in the lungs, was previously identified only in HLA-DR17 positive Scandinavian Caucasian sarcoidosis patients [20,22]. In fact, the association between lung accumulated CD4z AV2S3z T-lymphocytes and HLA-DR17 in Scandinavian patients with pulmonary sarcoidosis is extremely strict, provided there is an active disease [20,22]. Moreover, BAL AV2S3z T-cells were recently found to correlate with clinical features of the disease [23] and to express a panel of activation markers indicative of select stimulation of this particular subset [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation